Photo-activated emitting defects in the Ce-doped CaSnF6 fluoride. (October 2021) - Andron, Ines; Frayret, Christine; Gaudon, Manuel; Fargues, Alexandre; Durand, Etienne; Duttine, Mathieu; Toulemonde, Olivier; Jubera, Véronique
Graphical abstract: Highlights: UV and visible emission originated from Cerium doping in CaSnF6 . Impact of synthesis on photochromism effect in stannate compound. Modification of photochromism in Cerium doped stannate linked to thermal history. Abstract: Considering the interest to develop new photochromic compounds, the Ce doped-CaSnF6 have been selected and thoroughly characterized. After optimization of the synthesis route, the structural and morphological properties, are described. The origin of the optical properties and photochromic are supported by magnetic, RPE, 119 Sn Mossbauer, 19 F and 1 H MAS NMR characterizations. In addition to the UV luminescence of Ce 3+ ions in the stannate compound, they revealed the impact point defects at the origin of an additional visible contribution to the global signal. In view of elucidating the relationships between the observed photochromism and the possible nature of these defects, experimental interpretations are discussed on the basis of a computational approach.